The call center option a case study on employee work motivation in a call center (2009)
This study explored the work motivation of call center agents in one of the biggest call centers in the Philippines. It focused on the various factors existing within the company, which call center agents deem relatively important to their employment attraction, employee retention, and work effort. Results of the study indicate that it is largely the basic salary and the cash-based components of the compensation package the respondents receive which influenced their initial desire to apply for a job in the call center and their motivation to stay and work hard.
Keywords: Call centers; Call centers -- Employees (Philippines. Supreme Court)